Development of Lecithin Nanoemulsion Based Organogels for Permeation Enhancement of Metoprolol through Rat Skin. (14th November 2013) - Varshosaz, J.; Andalib, S.; Tabbakhian, M.; Ebrahimzadeh, N.
Abstract : Background . Drugs with low oral bioavailability due to the first pass metabolism are good candidates for transdermal delivery. Objectives. The aim of this work was preparation of transdermal nanoemulsion of metoprolol which has high first pass metabolism. Methods . Three commercially available types of lecithin (200, 100p, and 170), three short chain alcohol (n-butanol, isopropyl alcohol, and n-propanol), and isopropyl myristate (IPM) were used as surfactant, cosurfactant, and oil phase, respectively. The aqueous phase was composed of metoprolol tartrate. Nanoemulsions with different surfactant/cosurfactant weight ratio, various amounts of drug, and different types of alcohol were prepared, and their phase diagrams were studied. Drug release, permeability, and diffusion coefficient of the drug were studied using hairless rat skin. Results . A significant increase in drug solution rate was observed with increasing the metoprolol content in the nanoemulsions, while it decreased when lecithin concentration increased from 40% to 60%. Increasing the water content resulted in a significant increase in metoprolol release. N-butanol enhanced the drug flux from nanoemulsions more than n-propanol and isopropyl alcohol. The o/w nanoemulsions of metoprolol showed high flux and permeability through the skin. Conclusion . Both w/o and o/w nanoemulsions of metoprolol could enhance permeation and diffusion of metoprolol through rat skin.